2014
DOI: 10.1007/s40471-014-0014-4
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Socioeconomic Disparities in Heat-Related Health Effects and Their Mechanisms: a Review

Abstract: Adaptation to increasing extreme heat in a changing climate requires a precise understanding of who is most vulnerable to the health effects of extreme heat. The evidence for race, ethnicity, income, education and occupation, at the individual and area levels, as indicators of vulnerability is reviewed. The evidence for the social, behavioral and technological mechanisms by which racial and socioeconomic disparities in vulnerability exist is also reviewed. These characteristics include cardiorespiratory, renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
221
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(233 citation statements)
references
References 106 publications
(153 reference statements)
9
221
2
1
Order By: Relevance
“…This definition and measurement has been used in previous empirical studies on SHS among residents of the German cities Leipzig (Großmann et al, 2012), Aachen (Pfaffenbach and Siuda, 2010), and Nuremberg (Wittenberg et al, 2012). These clearly indicated that SHS in everyday life is not solely an issue at home and in the residential environment, but also at work.…”
Section: Factors Of Heat Stress In a Social Science Perspectivementioning
confidence: 97%
See 3 more Smart Citations
“…This definition and measurement has been used in previous empirical studies on SHS among residents of the German cities Leipzig (Großmann et al, 2012), Aachen (Pfaffenbach and Siuda, 2010), and Nuremberg (Wittenberg et al, 2012). These clearly indicated that SHS in everyday life is not solely an issue at home and in the residential environment, but also at work.…”
Section: Factors Of Heat Stress In a Social Science Perspectivementioning
confidence: 97%
“…stress (Großmann et al, 2012;Pfaffenbach and Siuda, 2010). Subjective heat stress hereby refers to the individual and selfreported assessment of respondents to what extent they experience high summer temperature as stress.…”
Section: T Kunz-plapp Et Al: Factors Of Subjective Heat Stress Of Umentioning
confidence: 99%
See 2 more Smart Citations
“…A person's inability to regulate his/her thermal balance can be related to physiological factors, such as a deterioration of heat regulation due to age, medical conditions, or medications [36]. Behavioral mechanisms, such as maintaining hydration or refraining from overexertion, can be crucial.…”
Section: Implications For Science-based Urban Climate Policy To Impromentioning
confidence: 99%